Factors determining high efficiency of cyber athletes' preparation for competitions - Bolotin, A.; Bakayev, V.; Sushchenko, V.; You, C. (IOP Conf. Series: Materials Science and Engineering, 2019)
The conducted research identified factors that determine the high efficiency of cyber athletes' preparation for competitions. The key factors that determine the high efficiency of cyber athletes' preparation for competitions reported by the respondents included the availability of a scientifically justified training and preparation program for the cyber athletes, as well as psychological tools and methods to relieve high-level tension during the competition. The respondents also paid attention to such factors as monitoring the expenditure of functional reserves of the body during competitive activities, as well as recovery activities after the competitions, taking into account the individual features of the cyber athlete's body. Important factors also include objective assessment of the dynamics of the mental activity level during the training process, as well as the implementation of measures to combat adverse factors that affect cyber athletes in the course of their preparation for competitive activities. An analysis of the performance of athletes at various competitions in the period from 2016 to 2018 was conducted. The survey involved 73 respondents, including athletes and coaches.